Sustainable Innovations in Textile Chemistry and Dyes (Textile Science and Clothing Technology,, 2018)
This book details two elements of textile chemistry namely- sustainable/eco-friendly dyes and green chemistry. It presents latest topics in sustainable dyeing techniques, low impact dyeing methods, wool dyeing techniques and green chemistry. Certain case studies are also highlighted.